2013
DOI: 10.5539/jfr.v2n1p8
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effects of Natural Tenderizing Enzymes on Escherichia Coli and Listeria monocytogenes

Abstract: The objective of this study was to determine the antimicrobial activity of proteolytic, meat-tenderizing enzymes (papain and bromelain) against E. coli and L. monocytogenes at three different temperatures (5, 25 and 35°C). Two overnight cultures of E. coli JM109 and L. monocytogenes were separately suspended in 1% peptone water and exposed to a proteolytic enzyme (papain or bromelain) at three different temperatures. Bromelain concentrations (4 mg/ml) and (1 mg/ml) tested at 25°C against E. coli and L. monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(12 reference statements)
1
7
1
2
Order By: Relevance
“…Antibacterial activity of bromelain of A. comusus has been reported against E. coli and L. monocytogenes (Eshamah et al 2013), which displayed that a concentration of 4 mg/ mL bromelain was sufficient to inhibit the growth of E. coli, while a concentration of 1.0 mg/mL substantially reduced, but not abolished the growth of L. monocytogenes (Eshamah et al 2013). This report also suggested that Gram-positive bacteria are more susceptible to bromelain in comparison to Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 62%
“…Antibacterial activity of bromelain of A. comusus has been reported against E. coli and L. monocytogenes (Eshamah et al 2013), which displayed that a concentration of 4 mg/ mL bromelain was sufficient to inhibit the growth of E. coli, while a concentration of 1.0 mg/mL substantially reduced, but not abolished the growth of L. monocytogenes (Eshamah et al 2013). This report also suggested that Gram-positive bacteria are more susceptible to bromelain in comparison to Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 62%
“…The bromelain enzyme will break down and denature the protein constituent of bacterial cell walls. As the cell weakens it can allow small molecule to leak out [70]. Okoh et al [44] performed the antibacterial activity of the peel extract and showed a greater inhibition for Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella typhi.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…10 Bromelain particularly works as a proteolytic enzyme once it is bound to bacterial cell membrane, causing damage and inducing bacterial cell death. 11 …”
Section: Kata Kunci: Ananas Comosus L Merr Antimikroba Pseudomonasmentioning
confidence: 99%
“…The numbers of amino acids in the bacterial cell wall are thought to determine the antibacterial activity of proteolytic enzymes. 11 Saponins increases the permeability of the bacterial cell membrane, causing alteration of structure and function of the membrane, disrupting the surface tension of the cell wall, then allowing antibacterial substances to easily enter the cells and interfere the cell metabolism while denaturates proteins on the membrane so the cell membrane will be lysis. 19 Saponin selectively interacts with cholesterols on cell membrane, leaving a hole in the membrane.…”
Section: Antibacterial Mechanism Of Pineapple Fruit Extractmentioning
confidence: 99%